Maqashid Syari'ah Analysis Of Pregnant Women's Marriage: A Review Of Individual And Community Welfare - Saputra, Deris Arista (Al-Makki Publisher, 2023)
The increasingly widespread phenomenon of promiscuity shows a decline in morals and moral values among adolescents, which has an impact on the problem of adultery and increasing cases of pregnancy outside marriage. Whereas in the Islamic view, marriage is a solution to avoid adultery, but if adultery is committed it becomes a serious violation of religious teachings. This study aims to determine the legal and ethical considerations in marriage dispensation due to pregnancy out of wedlock and to determine the consideration of Maqasid Shari'ah in determining marriage dispensation due to pregnancy outside marriage. The research method used in this study is literature research, through data from sources relevant to the research, such as books and journals that discuss the analysis of Maqashid Shari'ah on the marriage of women in a pregnant state. Descriptive analysis is carried out to identify and describe various aspects, regulations, and norms related to research. The results of the study show that legal and ethical considerations in marriage dispensation due to pregnancy out of wedlock are important to maintain the benefit of individuals and society. Marriage dispensations should carefully consider the age limits on marriage, individual rights, the protection of unborn children, and their social impacts. The principles of Maqasid Shari'ah, such as the protection of religion, soul, offspring, property, and honor, serve as important guidelines in maintaining a balance between religious values and social norms in the establishment of marriage dispensation due to pregnancy out of wedlock.